(untitled) (Indonesian Journal of Counseling and Development, 2023)
This research aims to conduct a comprehensive literature analysis, employing a comparative synthesis process, to elucidate the distinctive features of two counseling approaches rooted in the transpersonal psychology paradigm. The objective is to scrutinize, compare, and synthesize the perspectives, focal points, techniques, and outcomes inherent in these two transpersonal approaches. This endeavor is imperative in light of the growing demand for therapeutic methodologies grounded in spiritual dimensions and belief systems encompassing forces beyond the confines of human material existence. The employed methodology involves a thorough literature study, culminating in the synthesis of the two transpersonal paradigms. The resultant synthesis is intended to serve as a robust reference for forthcoming therapeutic counseling practices. By doing so, it aims to contribute to the ongoing evolution of more specialized counseling models within an expanding transpersonal paradigm. This synthesis, in turn, is poised to serve as a cornerstone for counseling models that transcend the constraints of materialism and modernis